Mitigating Aflatoxin Contamination in Groundnuts Using Plant-Derived Essential Oils: Implications for Food Security - Fredrick A. Obedi; Regina P. Mtei; Kessy F. Kilulya (Journal of Food Quality)
The production and storage of food crops in various households are affected by aflatoxin contamination, which comprises toxic and carcinogenic chemicals to both humans and animals. Aflatoxins, produced by Aspergillus flavus and Aspergillus parasiticus, impact several agricultural crops, notably maize, groundnuts, and spices. This study investigated the inhibitory potential of plant-based essential oils (EOs) (clove, cardamom, and garlic) in controlling mold growth and aflatoxin contamination in groundnuts by examining their impact on A. flavus growth. The EOs were extracted through hydrodistillation, and their chemical compositions were analyzed using gas chromatography–mass spectrometry (GC–MS), revealing dominant compounds such as eugenol (39.88%) in clove, alpha-terpineol acetate (36.50%) in cardamom, and trisulfide di-2 propenyl (51.72%) in garlic. The antifungal activities of these oils were evaluated using the agar diffusion method against A. flavus, showing that clove and cardamom oils could perfectly inhibit mycelial growth at concentrations ≥ 250 ppm. Clove oil demonstrated a 92% growth inhibition rate, and cardamom oil showed an 88% reduction, underscoring their potential as natural, safe alternatives for controlling aflatoxin contamination in stored groundnuts, thereby contributing to enhanced food security and health effects associated with aflatoxins.